Tick phenology, tick-host associations, and tick-borne pathogen surveillance in a recreational forest of East Texas, USA - Jordan Salomon; Haydee Montemayor; Cassandra Durden; Dorcas Abiara; Rachel E. Busselman; Gabriel L. Hamer; Sarah A. Hamer (PLoS ONE, 2025)
Management of tick-borne disease necessitates an understanding of tick phenology, tick-host associations, and pathogen dynamics. In a recreational hotspot outside of one of the largest cities in the United States, we conducted a year of monthly standardized tick drag sampling and wildlife trapping in Sam Houston National Forest, a high use recreation site near Houston in east Texas, US. By sampling 150 wildlife hosts of 18 species, including rodents, meso-mammals, deer, reptiles, and amphibians, we collected 87 blood samples, 90 ear biopsies, and 861 ticks representing four species (Amblyomma americanum, Dermacentor variabilis, Ixodes scapularis and Ixodes texanus). Drag sampling yielded 1,651 questing ticks of three species: A. americanum (921), D. variabilis (10), and I. scapularis (720). Off-host larval A. americanum abundance peaked in July, followed by peak infestations of wildlife, predominantly raccoons, in August. Off-host I. scapularis larvae abundance peaked in spring (March-May), while very few were removed from hosts and only a single I. scapularis nymph was found throughout the study via dragging in June. In contrast, both off-host and on-host adult I. scapularis occurred most frequently in the winter. Overall, tick infections included 25.3% (183/725) with Rickettsia buchneri, 15.5% (112/725) Rickettsia amblyommatis, 8.0% (58/725) Rickettsia tillamookensis, 0.8% (6/725) Rickettsia spp., and a single tick with a hard tick relapsing fever Borrelia spp.; no tick tested positive for Borrelia burgdorferi. Characterizing tick phenology, tick-host associations, and tick-borne bacteria fills important knowledge gaps for the risk of tick-borne diseases in pine-dominated forests of this region.